2007
DOI: 10.1111/j.1478-3231.2006.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Viusid, a nutritional supplement, in combination with interferon α‐2b and ribavirin in patients with chronic hepatitis C

Abstract: Our results suggest that triple therapy with Viusid, IFN alpha-2b and ribavirin was well tolerated and may have a beneficial effect on histologic and biochemical variables. The intensity of anemia is reduced in patients treated with Viusid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…A recent trial has suggested that viusid therapy combined with SOC in patients with chronic hepatitis C may reduce inflammation and fibrosis, irrespective of virological response 32. Another recently published study has reported a dual role to explain possible mechanisms of action of viusid on liver histology 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent trial has suggested that viusid therapy combined with SOC in patients with chronic hepatitis C may reduce inflammation and fibrosis, irrespective of virological response 32. Another recently published study has reported a dual role to explain possible mechanisms of action of viusid on liver histology 33.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging effects of viusid on liver histology have been reported in patients with non-alcoholic fatty liver disease and chronic hepatitis C 31 32. The authors reported that the addition of viusid to the conventional interferon/ribavirin therapy was associated with significant histological and biochemical improvements, especially in patients without a sustained virological response.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging effects of Viusid on liver histology have been reported in patients with chronic hepatitis C treated with unmodified interferon and ribavirin 31 . The mechanisms responsible for explaining the effect of Viusid on liver histology remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vilar Gomez et al. 31 evaluated the efficacy and safety of Viusid in combination with interferon alpha‐2b and ribavirin in patients with chronic hepatitis C. The authors reported that the addition of Viusid to the conventional interferon/ribavirin therapy was associated with significant histological and biochemical improvements, especially in patients without sustained virological response. They suggested that the Viusid‐related effect on histological features, especially fibrosis, appears to be associated with hepatoprotective or antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Its formulation comprises licorice extract, several vitamins such as ascorbic acid or B group vitamins or amino acids ( 5 ). This combination has demonstrated to improve clinical outcomes in several scenarios, such as patients with chronic hepatitis C that did not respond to standard antiviral treatments or interferon therapy ( 4 , 6 ), cirrhotic patients who have failed to achieve sustained virological response with standard of care treatments ( 5 ) or in combination with diet and exercise, to improve fatty liver disease ( 7 ). However, the mechanism of action of VS has not been fully elucidated, and research in this direction could potentiate its application to different pathologies.…”
Section: Introductionmentioning
confidence: 99%